A Brief Measure of Staff Commitment to Implement School-Wide Positive Behavioral Interventions and Supports. (December 2016) - Filter, Kevin J.; Sytsma, Marcia R.; McIntosh, Kent
Staff buy-in has been implicated as an important factor in the implementation of school-wide positive behavioral interventions and supports (SW-PBIS). However, most evidence related to buy-in is indirect and does not involve systematic measurement of buy-in. The purpose of the present study was to develop and evaluate a six-item measure of staff commitment to implement SW-PBIS. Responses were gathered from 1, 218 teachers and staff working in schools at various stages of SW-PBIS implementation. Results showed strong evidence of internal consistency, construct validity, and content validity for the buy-in measure. There was a strong bias toward positive responding on the measure, but there were statistically significant differences that aligned with previous research (e.g., grade level of the school, role of respondents). In terms of concurrent validity, the relation between commitment and fidelity of implementation was as hypothesized, but the low number of schools and limited variability made the findings tentative.